Membaca Ulang Konsep Perwalian Dalam Perspektif Mohammed Arkoun - Wahyudi, Muhammad Isna (Musawa Jurnal Studi Gender dan Islam, 2007)
Along with the development of human awareness on gender injustice, the provision of wali in Islamic law needs rethinking. Under the mainstream Islamic law a woman cannot marry off herselfbut a widow. It is only the wali of that woman who can marry her off in a marriage contract. Of course, in the outset such provision seems to be gender bias, because the Islamic law treats woman as incapable person. In order to examine this issue, Mohammad Arkoun has offered what he called as critics of Islamic reason. By applying a deconstruction method and fallowing archeology of knowledge we will be able to reveal the unthinkable issues of Islamic tradition. In this way, we can clarify and understand the issue of waliclearly, criticize the prevailingprovision on wali, and reconstruct the concept of wali in accordance with the present context